Case Report: Delayed Post-partum Preeclampsia in rural Ecuador - Miguel Obregón; Carolina Betancourt; David Gaus (Fundación Salud y Desarrollo Andino, Saludesa Ecuador, 2017)
Background: Delayed, Post-partum preeclampsia is an unusual presentation of preeclampsia.  Delay in diagnosis at the time of presentation could result in progression to eclampsia.  Consideration should be given to routine post-partum checkup at 3-4 weeks rather than 6 weeks in countries where home birthing is still common. Case Presentation: We report a case of delayed, post-partum preeclampsia in a mother 4 weeks post-partum who presented to our emergency department with headache and abdominal pain. Hypertensive urgency was diagnosed.  Subsequently, a 24 hour urine indicated significant proteinuria, and delayed postpartum preeclampsia was established.  Her blood pressure normalized and adequate diuresis was maintained.  Magnesium Sulfate was not initiated. Conclusion: A high index of suspicion for preeclampsia is required in hypertension in the peripartum period.  This is also true up to one month post partum.  When should magnesium sulfate be discontinued in these patients who have adequate diuresis and normal blood presssures, the signs normally used in the immediate post-partum period that the preeclampsia has resolved?